Immunogenicity and safety of adenovirus-based vector vaccines for COVID-19: a systematic review and meta-analysis (Faculty of Medicine Universitas Indonesia, 2021)
BACKGROUND Despite various research on vaccine development, severe acute respiratory syndrome coronavirus 2 infection continues to spread. Thus, developing a more effective vaccine for production and clinical efficacy is still in high demand. This review aimed to assess the immunogenicity and safety of adenovirus-based vector vaccine (Ad-vaccines) including Ad5-vectored, ChAdOx1 nCoV-19, rAd26-S or rAd5-S, and Ad26.COV2.S as the promising solutions for COVID-19. METHODS We conducted a systematic review and meta analysis of clinical trials based on the preferred reporting items for systematic reviews and meta-analyses guidelines through PubMed, Scopus, Cochrane, and EBSCOhost until August 17, 2021. We implemented inclusion and exclusion criteria and assessed the studies using OHAT risk of bias rating tool for human and animal studies. Pooled estimates of odds ratio (OR) were analyzed using fixed-effect model. RESULTS This systematic review yielded 12 clinical studies with a total of 75,105 subjects. Although the studies were heterogeneous, this meta-analysis showed that Ad-vaccine significantly increased protection and immune response against COVID-19 with a pooled efficacy of 84.68% compared to placebo (p<0.00001). Forest plot also indicated that Ad-vaccine conferred protection against moderate to severe COVID-19 with a pooled OR of 0.26 (p<0.00001). Ad-vaccine had also shown a good safety profile with local site pain and fever as the most common side effects. CONCLUSIONS Ad-vaccine had shown a good immunogenicity for COVID-19 with a good pooled efficacy and was proven safe for COVID-19 patients.